Interplay between many body effects and Coulomb screening in the optical bandgap of atomically thin MoS2 - Park, Y; Han, S; Chan, C; Reid, B; Taylor, R; Kim, N; Jo, Y; Im, H; Kim, K (Royal Society of Chemistry, 2017)
Due to its unique layer-number dependent electronic band structure and strong excitonic features, atomically thin MoS2 is an ideal 2D system where intriguing photoexcited-carrier-induced phenomena can be detected in excitonic luminescence. We perform micro-photoluminescence (PL) measurements and observe that the PL peak redshifts nonlinearly in mono- and bi-layer MoS2 as the excitation power is increased. The excited carrier-induced optical bandgap shrinkage is found to be proportional to n4/3, where n is the optically-induced free carrier density. The large exponent value of 4/3 is explicitly distinguished from a typical value of 1/3 in various semiconductor quantum well systems. The peculiar n4/3 dependent optical bandgap redshift may be due to the interplay between bandgap renormalization and reduced exciton binding energy.